GLN27GLU polymorphism in the β2-adrenergic receptor gene in patients with bronchial asthma - V. V. Kachkovska (Zaporožskij Medicinskij Žurnal)
The aim of the study was to analyze the frequency of the polymorphism in the β2-adrenoceptor (Gln27Glu) gene in patients with bronchial asthma (BA) and to assess the association of the polymorphism with disease risks.